2011
DOI: 10.1152/japplphysiol.00162.2011
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoconstriction in nonhuman primates: a species comparison

Abstract: Bronchoconstriction is a characteristic symptom of various chronic obstructive respiratory diseases such as chronic obstructive pulmonary disease and asthma. Precision-cut lung slices (PCLS) are a suitable ex vivo model to study physiological mechanisms of bronchoconstriction in different species. In the present study, we established an ex vivo model of bronchoconstriction in nonhuman primates (NHPs). PCLS prepared from common marmosets, cynomolgus macaques, rhesus macaques, and anubis baboons were stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 58 publications
0
57
0
Order By: Relevance
“…Previous work on this technology have shown that PCLS can easily be prepared in abundance just from a single human lung lobe and can be prepared from human as well as different laboratory animal species, including mice, rats, guinea pigs, sheep and monkeys. [1][2][3][4][5] Multiple studies have focused on assessing various characteristics of cultured PCLS, such as measurement of bronchoconstriction [6][7][8] and vascular responses 9,10 induced by various stimuli. In addition, PCLS have been used to evaluate allergy, 11 asthma, 6 toxicology, [12][13][14] and infectious disease responses.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on this technology have shown that PCLS can easily be prepared in abundance just from a single human lung lobe and can be prepared from human as well as different laboratory animal species, including mice, rats, guinea pigs, sheep and monkeys. [1][2][3][4][5] Multiple studies have focused on assessing various characteristics of cultured PCLS, such as measurement of bronchoconstriction [6][7][8] and vascular responses 9,10 induced by various stimuli. In addition, PCLS have been used to evaluate allergy, 11 asthma, 6 toxicology, [12][13][14] and infectious disease responses.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has demonstrated the high sensitivity of guinea pigs' (EC50=217 nM) (Ressemeyer et al 2006) and marmosets' (EC50=425 nM) (Seehase et al 2011) small airways to histamine. Studies on the horse provided variable results.…”
Section: Discussionmentioning
confidence: 99%
“…The microarchitecture of lung tissue, i.e. airways and vessels embedded in the parenchyma, remains intact and permit physiological measurements [23][24][25][26]. Even nerves remain functional and can be specifically activated [29].…”
Section: Discussionmentioning
confidence: 99%
“…PCLS can easily be prepared from different species and are already established for many species including rat, mouse, guinea pig, non-human primates and humans [14,17,[23][24][25][26]. PCLS represent a highly useful model to study bronchial and pulmonary vascular responses by videomicroscopy [23,27].…”
Section: Introductionmentioning
confidence: 99%